Kleptoparasitism and Coexistence: Resource Competition Between Indian Leopards and Striped Hyenas - Reuven Yosef; Swapnil Kumbhojkar (Animals)
In ecosystems where multiple carnivores coexist, interspecific interactions are crucial in shaping behavioral adaptations and resource utilization strategies. This study examines the competitive dynamics between Indian leopards (Panthera pardus fusca) and striped hyenas (Hyaena hyaena) in the Jhalana Reserve Forest, an urban-enclosed wildlife habitat in Jaipur, India. Using direct observations, citizen science contributions, and camera-trap data, we document kleptoparasitism and competitive exclusion instances where hyenas successfully outnumber leopards to gain access to food. Our findings indicate that hyenas exhibit an acute ability to locate leopard kills, often arriving within minutes of a leopard beginning to feed. Additionally, spatial constraints imposed by the reserve’s fencing create an ecological imbalance, as leopards can access external food sources while hyenas remain confined. We also discuss the potential consequences of supplementary feeding practices, which may influence predator behavior and interspecific interactions. This study highlights the importance of understanding competitive dynamics in fragmented landscapes to inform conservation strategies that promote coexistence.